Juridical Deed Review Of The Cooperation Agreement To Build Handover (Build Operate And Transfer) Bot Between Government And Private Sector - Desi Wulan Anggraini; Bagus Langgeng Prasetiyo; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) To determine and analyze the Agreement in order to handover a build (Build Operate And Transfer) BOT between government with Private Sector. 2) To determine and analyze the Regulation No. 19 of 2016 there are no relevant provisions of the cooperation agreement made in the form of a notarial deed but in implementing cooperation agreements and there are other legal regulations. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analytical method.Based on the results of data analysis concluded that: 1) Deed in the agreement to transfer (Build Operate And Transfer / BOT) before the formation of Regulation No. 19 of 2016, has complied with the requirements valid agreement of Article 1320 of the Civil Code sehigga positions of the legislation. Notary deed in agreement wake up in order to transfer (Build Operate and Transfer) BOT after the entry into force of Regulation No. 19, 2016 a requirement valid agreement beyond the provisions of the Civil Code, and if it is not done then there will never been considered although qualify valid agreement of Article 1320 of the Civil Code. The legal consequences deed of cancellation of the parties shall make a certificate into a build to transfer (Build Operate Transfer / BOT) lose their authenticity, the cancellation of the agreement unilaterally because defaults are not eligible void Article 1266 of the Civil Code, can be regarded as an act against the law because it is not based on good faith and such cancellation shall be requested to the trial judge.Keywords: Judicial Review; Government Cooperation Agreement; Build Operate and Transfer And Deed.